Assessing Energy Source Preference of Household and Stand Diversity in the Catchment Area of Bamako, Mali - Coulibaly, Oumar; Ballo, Abdou; Cissoko, Fousseny (European Scientific Journal, ESJ, 2021)
Wood fuel as a domestic combustible plays a major role for the Malian population (more than 90% of households depend on it for domestic cooking). It is used in rural as well as in urban areas. This paper focuses on assessing the energy source preference of households and stand diversity in Bamako catchment area. We have surveyed 200 households and 70 firewood and charcoal sellers in the District of Bamako. Forest inventory was carried out in Famana and Kassela within the Bamako catchment area where plots have been established (10 plots of 50 x 20 m per site). Plots were separated from each other by 50m. Results showed that the use of charcoal is higher than firewood in the urban households due to its availability and easy handling. 71.50% of households in Bamako use charcoal for cooking meals. Charcoal has become the most preferred source of energy for households in Bamako. The main factors for this trend are related to poverty, cooking habits of households, and urbanization. The two sites (Famana and Faya) are characterized by high diversity. Famana has a Shannon Diversity Index of 2.92 while Faya has 2.55. The study revealed a strong capacity of woody formations to provide species such as Combretum glutinosum, Combretum micranthum, and Lannea velutina which is very convenient for domestic combustion. These species have a rapid regeneration capacity and can grow in many types of ecological environments. Species such as Parkia biglobosa, Vittelaria paradoxa, Ficus gnaphalocarpa, and Khaya senegalensis (protected species) that are highly appreciated by households of Bamako have a great economic value and are constantly under threat. Households demand for these species exceeds the production capacity of forests. Immediate actions are needed to promote modern energy in order to ensure sustainable development.